Neuromuscular performance and balance during the menstrual cycle and the influence of premenstrual symptoms - Friden, C. (2004)
Several studies have demonstrated a higher incidence of sports related knee injuries among female athletes compared to their male counterparts regardless of exposure time and activity level. Different intrinsic and extrinsic factors have been proposed as risk factors in women. The hormonal variation during the menstrual cycle has been suggested as one of the intrinsic factors and an association between sport injuries in female athletes and the menstrual cycle has been reported. An increased injury rate has been observed during the premenstrual and menstrual phase, whereas one author reported a higher incidence during the ovulatory phase. It has been suggested that impaired neuromuscular function due to the specific hormonal influence of the menstrual cycle contributes to the association between sport injuries and different phases of the menstrual cycle. Furthermore, women with premenstrual symptoms (PMS) have been shown to be at greater risk of injury compared to women without PMS.